PERAN PBB DALAM MENANGGULANGI VIOLENCE AGAINST WOMEN (VAW) OLEH KELOMPOK EKSTRIMIS ISIS DI NEGARA KONFLIK SURIAH TAHUN 2013-2016 - Fanny Adita; Yuli Fachri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describes the role of United Nations to handle violence against women by Islamic State (IS) in Syria Arab Republic conflict that began in 2013. The Islamic State is one of the main actors of the conflict in Syria that makes the conflict worse. The Islamic State is a extremist group that uses sadism violence to establish a state based on khilafah Islamiyah system. Since the conflict began womens in Syrian faced situations that risk their right. IS treats women in Syria with inhumanity such as arrest and torture, as sex slaves, murders, genocide.This research use Pluralism perspective of International Relations. Pluralism believe state is not the only actor in international world. This research is also guide by international organization theory and role concept. Fact, data, arguments, and theorical framework of this research formulate by using qualitative description.This research intended to show the role of United Nations as conflict resolver at the humanitarian crisis caused Islamic State in Syria Arab Republic. United Nations through United Nations Human Right Council (UNHRC) investigating violations and calling for the protection of the human rights of the citizens of Syria Arab Republic. And also with the Security Council and The International Community making a resolution against the existence of Islamic State.Keywords : UNHRC, Violence Against Women, Islamic State, Syria